2022
DOI: 10.1007/s11845-021-02868-w
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition improves COVID-19 clinical progress

Abstract: Nutrition is a basic need and is crucial for the persistence of good health. This awareness has increased since December 2019 during the pandemic that the world is still facing. The importance of nutrition in infectious diseases was emphasized but the relationship between the severity of symptoms and nutrition status of individuals was not examined. This study compared the nutrition status of patients with COVID-19 admitted to the emergency service and the clinical severity of the disease. Based on the nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Age is a factor that is directly associated with the risk of mortality due to COVID-19 [ 15 18 ]. Malnutrition is highly prevalent in elderly patients and may partially account for this elevated mortality risk given its links with severe disease [ 6 , 19 , 20 ]. In the present study on critically ill COVID-19 patients, those who died had a greater mean age than those who recovered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age is a factor that is directly associated with the risk of mortality due to COVID-19 [ 15 18 ]. Malnutrition is highly prevalent in elderly patients and may partially account for this elevated mortality risk given its links with severe disease [ 6 , 19 , 20 ]. In the present study on critically ill COVID-19 patients, those who died had a greater mean age than those who recovered.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that those with a higher age also had a higher risk of malnutrition, as reported by Alikiaii et al [ 21 ]. This is significant because the interaction between malnutrition and COVID-19 risk and severity seems to be bidirectional, with each able to affect the other [ 20 , 22 ]. One study reviewed 4,187 hospitalized COVID-19 patients and revealed ten-fold higher odds of mortality among those who were malnourished relative to well-nourished individuals [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis revealed that three out of ten adults in the UAE suffer from hypertension [ 14 ]. Given that obesity and these associated diseases are known risk factors for severe COVID-19 outcomes and associated mortality [ 15 ], the role of dieticians is critical in tailoring nutritional guidance and support to patients, helping them make informed choices to improve their overall health and strengthen their immune systems [ 16 ].…”
Section: Introductionmentioning
confidence: 99%